Influence of Eco Process Pozzolan on the properties of Foamed Concrete - Rokiah, Othman; Nasly, Mohamed Ali; Khairunisa, Muthusamy (2015)
Present research studies the effect of Eco Process Pozzolan (EPP) on the properties of foamed concrete as replacement for cement. Uses of EPP replace cement in the proportions of 10, 20, 30, and 40 percent by weight of binder. The influences of EPP as partial cement replacement on workability, density, compressive strength, and water absorption of foamed concrete have been reported. Results indicate that EPP significantly improved the compressive strength of foamed concrete and other properties also performed well which behaviours are comparable to normal concrete.